REMARKS BY ELLEN MERLO VICE PRESIDENT,CORPORATE AFFAIRS PHILIP MORRIS U.S.A. PHILIP MORRIS U.S.A. VENDOR CONFERENCE GRAND HYATT HOTEL NEW YORK CITY TUESDAY, 940125 - MERLO,E (Tufts Archival Research Center, 2007)
Pages Out of Order; Marginalia; Draft; Draft of a speech given at the Philip Morris, U.S.A. Vendor Conference. Identifies three priority issues for 1994: excise tax, smoking restrictions, and marketing restriction. Encourages preemptive legislation, coalition building, and advocacy. Emphasizes the Accommodation Program in combating smoking restrictions. Explains dangers of referenda in reference to excise taxes.